2020
DOI: 10.1051/ocl/2020063
|View full text |Cite|
|
Sign up to set email alerts
|

Selections of donors depending on agronomic traits, seed yield components, and fatty acid profile for genetic improvement of Carthamus using stepwise multiple regression

Abstract: Safflower (Carthamus tinctorius L.) is of potential interest to agriculture due to mainly variability of fatty acid composition of seeds oil. The purpose of this study was to evaluate various exotic genotypes of safflower for agronomic traits, components of seed yield and fatty acid content. For this purpose, plant height (cm), number of first, second and third branches/plant, seed yield/plant (g), thousand-seed weight (g), oil content (%), and composition of fatty acid were investigated. Stepwise multiple reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…Ultimately, number of twin pods showed negative association (p < 0.01) with crude fibre of seed ( β = − 0.518). This finding is consistent with those reported by Hintz, and Albrecht 64 and Yassein et al 65 who reported that morphological characteristics correlated with seed oil content of Safflower ( Carthamus tinctorius L.), and crude fibre and protein content of alfalfa ( Medicago sativa L.) forage. Thus, multiple regression analysis can improve the accuracy of predicting leaf and seed proximate composition such as fat, protein and crude fibre.…”
Section: Resultssupporting
confidence: 93%
“…Ultimately, number of twin pods showed negative association (p < 0.01) with crude fibre of seed ( β = − 0.518). This finding is consistent with those reported by Hintz, and Albrecht 64 and Yassein et al 65 who reported that morphological characteristics correlated with seed oil content of Safflower ( Carthamus tinctorius L.), and crude fibre and protein content of alfalfa ( Medicago sativa L.) forage. Thus, multiple regression analysis can improve the accuracy of predicting leaf and seed proximate composition such as fat, protein and crude fibre.…”
Section: Resultssupporting
confidence: 93%
“…Safflower is an oleaginous species of significant interest due to its fatty acid variability content in the seed oil [47,48]. Our study indicates that extracted oil is very rich in unsaturated fatty acids, where their rate has reached a maximum value of 90.59% (Halab) and 90.81% (Gila).…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, in addition to rainfall, seed yield per plant was probably higher in these locations. Seed yield and oil content are the most important criteria in safflower breeding (Erbaş et al, 2023; Kose et al, 2018; Yassein et al, 2020), so it is important to investigate the cold tolerance abilities of genotypes before any breeding program is initiated. Studies have shown that safflower seed yield varies considerably in different environmental conditions and locations (Erbaş et al, 2023; Zanetti et al, 2022).…”
Section: Resultsmentioning
confidence: 99%